Development of Technical Safety Dashboard Using Microsoft Power BI Integration with R - Mohd Shamim, Nur Farisha Shuhada (IRC, 2020)
Presenting Technical Safety Dashboard using PETRONAS Analytical Toolkit (PETTA) tool is the normal practice for meetings that require updates on projects. Recently, the performance of PETTA is declining and this is one the main problems that hinder the executives from having a good data display and data visualization during meetings. Having documentation on the dashboard report also has been an issue when executive need to extract information manually from the dashboard. Besides, this paper also enlightens on one of the Machine Learning tools used which is R, with the utilization of K Nearest Neighbor (KNN) algorithm as method of classification for data. This algorithm has been used to forecast on the end date of projects. Thus, this research and project is made to deepen the usage of the substitute of PETTA, which is also dashboard creator tools which is powered by Microsoft, known as Power BI and also the utilization of machine learning to have data prediction. As to perform these studies, literature review has been executed together with the prototype development. In this paper, all researches and results of this project development completely documented.